2017
DOI: 10.4172/2155-6199.1000396
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Technical and Economic Feasibility of Complete Bioremediation for Soils Chronically Polluted with Petroleum Hydrocarbons

Abstract: Petroleum hydrocarbons are highly persistent in the environment and represent a significant risk for humans, biodiversity, and the ecosystems. Frequently, hydrocarbon-contaminated sites remain polluted for decades due to a lack of proper decontamination treatments. Although bioremediation techniques have gained attention for being environmentally friendly, cost-effective and applicable in situ, their application is still limited. Each polluted soil has particularities, therefore, the bioremediation approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(70 reference statements)
0
5
0
1
Order By: Relevance
“…Economic assessment was made based on the results of bioremediation of five treatments to clean-up chronically hydrocarbon-contaminated soils, based on bioaugmentation, biostimulation or combination of both technologies [52]. The first approach was bioaugmentation, with the addition of five hydrocarbonoclastic strains (named as BA).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Economic assessment was made based on the results of bioremediation of five treatments to clean-up chronically hydrocarbon-contaminated soils, based on bioaugmentation, biostimulation or combination of both technologies [52]. The first approach was bioaugmentation, with the addition of five hydrocarbonoclastic strains (named as BA).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that biostimulation-based treatments have lower costs than their counterparts using bioaugmentation. Specifically, the comparison between all bioaugmented treatments and BE1 revealed that the last treatment, though effective in hydrocarbon biodegradation [52], showed a significant reduction in direct material costs, provision and covering assets. This highlights the properties of compost, which is the mature product of composting, a bioprocess that transform solid organic substrates into relatively stable, organic-rich material via microbial communities [60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Кроме того, эффективное обезвреживание нефтеотходов и ликвидация амбаров-накопителей по-прежнему остается актуальной задачей нефтехимических предприятий. С одной стороны, это связано с высокой устойчивостью нефтешламов к разрушению, особенностями их состава и свойств, которые постоянно меняются под воздействием погодных условий и процессов, протекающих в них [15][16][17]. С другой стороны, нефтеперерабатывающие предприятия при обращении с нефтеотходами должны минимизировать их количество, разрабатывать собственные экономически доступные и технически осуществимые технологии для вовлечения отходов в ресурсооборот.…”
Section: выводы и рекомендацииunclassified